1998
DOI: 10.1038/sj.bmt.1701219
|View full text |Cite
|
Sign up to set email alerts
|

Marrow repopulating cells in mobilized PBPC can be serially transplanted for up to five generations or be remobilized in PBPC reconstituted mice

Abstract: Summary:We have evaluated the durability of engraftment and the potential of remobilization in mice reconstituted with mobilized peripheral blood progenitor cells (PBPC). Female mice which had been reconstituted with cytokine-mobilized PBPC from male donors were serially transplanted into second, third, fourth and fifth lethally irradiated female recipients at intervals of 6-10 months. Male-derived hematopoiesis was determined in recipient mice at each serial transplantation. Male-positive CFCs were detected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…The large amount of accessory cells present in peripheral blood could potentially also allow for immunomodulatory approaches to enhance graft versus tumor response following transplantation [1,2]. While several authors have reported differences in the phenotype, cell cycle status, and amount of stem cells present in PBSC versus BMHSC [10][11][12][13][14][15][16][17][18][19][20][21], other research groups have devoted their attention to the mechanisms by which HSC are mobilized [22][23][24][25][26][27]. Still, a further understanding of the mechanisms of mobilization and the quality and biological characteristics of stem cell subsets in peripheral blood with respect to both the level and durability of engraftment they provide would likely contribute to the development of safer, more predictable and efficacious mobilization protocols with higher safety.…”
Section: Introductionmentioning
confidence: 99%
“…The large amount of accessory cells present in peripheral blood could potentially also allow for immunomodulatory approaches to enhance graft versus tumor response following transplantation [1,2]. While several authors have reported differences in the phenotype, cell cycle status, and amount of stem cells present in PBSC versus BMHSC [10][11][12][13][14][15][16][17][18][19][20][21], other research groups have devoted their attention to the mechanisms by which HSC are mobilized [22][23][24][25][26][27]. Still, a further understanding of the mechanisms of mobilization and the quality and biological characteristics of stem cell subsets in peripheral blood with respect to both the level and durability of engraftment they provide would likely contribute to the development of safer, more predictable and efficacious mobilization protocols with higher safety.…”
Section: Introductionmentioning
confidence: 99%